2020
DOI: 10.3390/v12010075
|View full text |Cite
|
Sign up to set email alerts
|

Envelope-Specific IgG3 and IgG1 Responses Are Associated with Clearance of Acute Hepatitis C Virus Infection

Abstract: Hepatitis C virus (HCV) can be cleared naturally in a subset of individuals. However, the asymptomatic nature of acute HCV infection makes the study of the early immune response and defining the correlates of protection challenging. Despite this, there is now strong evidence implicating the humoral immune response, specifically neutralising antibodies, in determining the clearance or chronicity outcomes of primary HCV infection. In general, immunoglobulin G (IgG) plays the major role in viral neutralisation. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 81 publications
6
39
0
Order By: Relevance
“…Previous studies have demonstrated that when compared with HCs, serum IgG1 and IgG3 levels were higher in virus-infected individuals (48). In the present study, IgG1/IgG levels were significantly increased in viral liver disease group when compared with HCs.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have demonstrated that when compared with HCs, serum IgG1 and IgG3 levels were higher in virus-infected individuals (48). In the present study, IgG1/IgG levels were significantly increased in viral liver disease group when compared with HCs.…”
Section: Discussionsupporting
confidence: 51%
“…Surprisingly, however, anti‐E IgA was significantly associated with HESN individuals when compared to the pre‐infection time point of incident individuals. In our previous report of serological responses during primary HCV infection, very few subjects had detectable anti‐HCV E IgA responses and there was no association with clearance 40 . Given the recognized role of polymeric IgA (pIgA) in mucosal protection, and the previous analysis of incident case samples from this cohort showing elevated serum levels of pIgA, 48 it may be of interest to further characterize these IgA responses.…”
Section: Discussionmentioning
confidence: 85%
“…These responses were almost exclusively in the IgG2 subclass. This finding is noteworthy as IgG2 responses are rare in primary HCV infection, 40 but do have unique functional characteristics of potential relevance to protective immunity. IgG2 antibodies are recognized to bind glycans independent of T‐cell help (typically targeting bacterial polysaccharides, but also viral glycans) 43,44 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These data suggested that the earlier and higher the NP-specific IgG and IgM appeared, the more likely HFRS developed mild disease. Prior studies have suggested that the deficiency of virus-specific IgG was associated with persistent viremia [22,23]. Hence, we examined plasma viral loads in HFRS patients by quantitative RT-PCR.…”
Section: Effective Np-specific Antibody Responses Associated With Htnmentioning
confidence: 98%